2023
DOI: 10.32598/ijvm.17.1.1005256
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Methicillin-resistant Staphylococcus aureus (MRSA) From Dairy Cows in Kebbi, Nigeria

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an important healthcare-associated pathogen that is also an emerging zoonosis. Objectives: A cross-sectional study was conducted to investigate the prevalence of MRSA in dairy cattle farms in Kebbi, North-Western Nigeria. Methods: A total of 200 milk samples, consisting of 50 samples each from lactating cows, were collected and used. The samples were analyzed using bacterial culture and isolation and polymerase chain reaction (PCR). Suspected M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…aureus in bovine and poultry isolates exhibiting diverse genotypes could give rise to a distinctive form of infection (9,33). There was a notable correlation between the expression of methicillin resistance at the phenotypic level and the detection of the mecA gene at the genotypic level (10,34). This study conducted genotypic detection of the and femA genes, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…aureus in bovine and poultry isolates exhibiting diverse genotypes could give rise to a distinctive form of infection (9,33). There was a notable correlation between the expression of methicillin resistance at the phenotypic level and the detection of the mecA gene at the genotypic level (10,34). This study conducted genotypic detection of the and femA genes, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that no resistance to vancomycin, gentamicin, ciprofloxacin and imipenem was observed, which is contrary to the findings of Gaddafi et al () in Iran who reported high resistance of isolates to penicillin, gentamicin and oxytetracycline. (10). The isolates were resistant to penicillin (57%), ampicillin (61.5%), erythromycin (34.6%), and sulfamethoxazole (5.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the identification of the mecA gene in all LA-MRSA isolates, as reported in the Silva et al 11 investigation from Quails in Portugal as well Gaddafi et al 33 from dairy cows in Nigeria, indicates its consistent presence and remains the definitive indicator for MRSA detection. mecA -positive staphylococcal strains, immune to all β-lactam antibiotics, highlight the significance of this genetic marker 34 .…”
Section: Discussionsupporting
confidence: 78%
“…Such extensively drug-resistant (XDR) strains are especially difficult to treat and are associated with poor clinical outcomes. Other studies have also identified multidrug-resistant S. aureus strains from milk and other dairy products and this portends a serious risk to animal and human health (Oloso et al, 2018;Oludairo et al, 2020;Sayed-Ahmed et al, 2020;Tibebu et al, 2021;Badawy et al, 2022;Murray et al, 2022;Alembo & Torka, 2023;Gaddafi et al, 2023). The multidrug resistance patterns expressed by the S. aureus isolates suggest a broader resistance profile, encompassing multiple antibiotic classes, which further complicates treatment options.…”
mentioning
confidence: 99%